2018
DOI: 10.1007/s00134-018-5148-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impact on mortality of prompt admission to critical care for deteriorating ward patients: an instrumental variable analysis using critical care bed strain

Abstract: PurposeTo estimate the effect of prompt admission to critical care on mortality for deteriorating ward patients.MethodsWe performed a prospective cohort study of consecutive ward patients assessed for critical care. Prompt admissions (within 4 h of assessment) were compared to a ‘watchful waiting’ cohort. We used critical care strain (bed occupancy) as a natural randomisation event that would predict prompt transfer to critical care. Strain was classified as low, medium or high (2+, 1 or 0 empty beds). This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 33 publications
4
62
1
1
Order By: Relevance
“…In general, DTOC is associated with high occupancy levels, which in turn has been shown to have detrimental effect on mortality due to the increased acuity of admitted patients ( 8 ). Our data support the previous findings that reducing congestion may improve timely access to critical care, with potentially improved patient outcomes ( 9 , 10 ). Based on our simulation data, with the planned increase first to 25 then to 28 critical care beds alone, the new hospital could still cope with the projected increase in admissions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, DTOC is associated with high occupancy levels, which in turn has been shown to have detrimental effect on mortality due to the increased acuity of admitted patients ( 8 ). Our data support the previous findings that reducing congestion may improve timely access to critical care, with potentially improved patient outcomes ( 9 , 10 ). Based on our simulation data, with the planned increase first to 25 then to 28 critical care beds alone, the new hospital could still cope with the projected increase in admissions.…”
Section: Discussionsupporting
confidence: 91%
“…There is a valid argument that with increased ICU bed strain, patients are admitted in a worse physiologic status, in turn increasing their LOS ( 8 , 26 ). DES models can be configured to add this element to the simulation; however, for our current model, we could not quantify the unmet need for critical care from the available data ( 9 ). Another limitation of the data was that we only recorded how many days a patient spent at each level of care and we assumed that they move through the system with decreasing level of dependency.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this article is the first to recognize that the effectiveness of ICU care may be modified according to patient characteristics that are unmeasured and those that are measured. 17 , 20 , 21 , 22 We estimate the effectiveness of ICU transfer according to patient age and illness severity alone and combined.…”
Section: Introductionmentioning
confidence: 99%
“…The trial showed a higher proportion of ICU admissions for elderly patients compared to usual care, but this practice was associated with an increased risk of long-term mortality in the intention-to-treat analysis [1,4]. In contrast, two recent observational studies using causal inference, showed the potential for short-term mortality benefit of ICU admission [7,8] in elderly patients with pneumonia [7]. The two key patient characteristics associated with poor outcomes in these studies were the presence of an underlying malignancy and disability at the time of ICU admission [2].…”
mentioning
confidence: 99%